ANALISIS IMPLEMENTASI SISTEM PENGENDALIAN INTERN PEMERINTAH DALAM KINERJA PELAYANAN DAN PENYUSUNAN LAPORAN KEUANGAN BADAN LAYANAN UMUM DAERAH : Studi pada BLUD Puskesmas Pabedilan, Kabupaten Cirebon - Istiqomah, Nur Ahfli; Nisa, Farhatun (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The Regional Public Service Agency (BLUD) was established by the Government in an effort to fulfill community services, and it is authorized financial management flexibility to support service delivery.  BLUD that is commonly found by the community is the Public Health Centre (Puskesmas), which is a first-level health facility that aims to provide optimal health services. The implementation of optimal health services is supported by policies that authorize BLUD to manage finances independently and then account for the authority by preparing financial reports. The implementation of BLUD necessitates the establishment of robust internal control mechanisms. These mechanisms are designed to ensure that BLUD operates in accordance with its objectives, while also mitigating potential health and financial risks. Research conducted at BLUD Puskesmas Pabedilan revealed that the internal control mechanisms at BLUD Puskesmas Pabedilan have endeavored to implement the five components of control in the performance of services and the preparation of financial statements. However, the study identified deficiencies in the supervision of medications and medical devices, the simultaneous holding of positions by internal auditors and financial managers, and the absence of an ideal internal control configurations